ANÁLISIS TOPOGRÁFICOS EN PACIENTES ADAPTADOS CON LENTES DE CONTACTO BLANDOS ESFÉRICOS HIDROGEL DE SILICONA (2014)
Objetive: Identify changes in patients tomographic patterns in soft lens wearers silicone hydrogel contact in clinical optometry at the Universidad of Santo Tomás Bucaramanga in 2014.Methods: A study of experimental quantitative masked randomized clinical trial was conducted in which the analysis of topographic changes of the cornea in patients who have adapted them two types of soft contact lenses silicone hydrogel spherical silvers. For the execution of this study, a composite of ten (10) participants shows, who were asked monitored monthly for 3 months, in which visual acuity, among other things features such as topographic indices were evaluated, is used.Results: According to the results, it was found that there were no clinically significant changes during the three months of lens wear, because the curvature and corneal thickness remained within the parameters of normality, even though there was a slight thinning and corneal edema.Conclusions: Although from the beginning some indexes such as the index offset by lifting index vertical asymmetry and asymmetry index elevation was found altered it should be noted that during the study with the use of contact lenses these rates remained the same, in some improved as in the case index by lifting runout.